New insight into the fabrication of smart mucoadhesive buccal patches as a novel controlled-drug delivery system. (October 2019) - Rohani Shirvan, Anahita; Bashari, Azadeh; Hemmatinejad, Nahid
Graphical abstract: Highlights: We provided a detailed understanding of buccal mucoadhesive patches. Some smart polymeric mucoadhesive materials for buccal mucoadhesive patches were reviewed. New designs and manufacturing methods for polymeric mucoadhesive films were described. Abstract: Buccal mucosa is considered as a convenient and easily accessible site for the drug administration for both local and systemic delivery. Mucoadhesion is a process involving chemical interactions between mucin and polymers. The use of mucoadhesive polymers in buccal drug delivery has gained a great attention. Various mucoadhesive dosage forms, including tablets, patches, disks, wafers, ointments and gels have recently been developed. Amongst them, buccal patches offer greater flexibility and comfort than the other forms. Smart materials such as stimuli-responsive hydrogels, liposome-based patches, polymeric micelles, etc. play a vital role in the development of these drug delivery systems by their efficient carrier capacity, prolonging the residence time of the drug at the site of absorption, improved drug bioavailability, reduced dosing frequency and improved patience compliance. There are different designs and manufacturing methods such as electrospinning, electrospraying and 3D printing techniques which are considered as novel and efficient methods for preparation of buccal patches with some unique characteristics than traditional approaches such as solvent casting. In this review, an attempt has been made to discuss and introduce the most promising smart polymeric materials, new designs and manufacturing methods for the development of buccal mucoadhesive patches as a new controlled drug delivery system.